Modelling mechanical systems - Levin, Ari (Department of Mechanical Engineering, 2016)
Education should be one of the highest priorities of any country. The ability to pass on knowledge and understanding effectively is a sign of a good educational system. From an engineering perspective, better teaching tools allow for greater understanding by the students making them better engineers. Educational aids have been with us for a long time. Inventions from the abacus to the personal computer, have aided engineering students in faster understanding and application of their work. These aids are costly and sometimes become affordable only when outdated and redundant. A low-cost device that does not date would be the educationalist's ideal solution. To this end, a concept model of a conveyor sorting system was developed using Lego as the design medium. The model is a conveyor belt along which coloured blocks are sorted into bins by pneumatic cylinders. The model is controlled by a personal computer and the Lego interface box. The software is written in Visual Basic.